Impact of ICT on Enhancing Knowledge Sharing of Employees - Jain, Dr. Supriya (International Journal of Advanced Science and Technology, 2020)
Purpose –Despite the growing prominence of in application of information and communication technology knowledge management, knowledge sharing and knowledge transfer practices in the organizations, limited studies examine this aspect. Design/methodology/approach– The paper draws on qualitative and quantitative evidence to assess the impact of ICT on knowledge sharing and management among employers. Findings - The study identified that ICT plays a significant role in improving the working efficiencies of the employees and is a significant contributor to organizational culture and competitiveness. Originality/value - There is a lack of research concerning the impact of ICT, which present unique challenges to the employees in an organization. This study contributes by proposing a framework for the enhancement of knowledge sharing of employees, thereby filling a gap in research on the role of ICT in the implementation of knowledge sharing. This study also provides insight into the knowledge sharing barriers that are reduced by ICT applications and includes detail about the transfer or codify tacit into explicit knowledge in organizations.